Identification of Major Bioactive Anti-inflammatory Compounds of Derris scandens Stem Using RAW 264.7 Cells and HPLC-UV Analysis - Sae-Foo, Worapol; Yusakul, Gorawit; Nualkaew, Natsajee; Putalun, Waraporn (Planta Medica, 2023)
Derris scandens (DS) is widely recognized for its therapeutic properties, specifically its analgesic effects, which significantly alleviate muscle pain. The chemical constituents of DS stem include various isoflavone derivatives. However, there is currently a lack of specified anti-inflammatory chemical markers and analytical methods for quality control. The present study aimed to evaluate the anti-inflammatory activity of DS and its constituents using the RAW 264.7 cell model. The expression of inflammatory genes such as inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-6 (IL-6), and 5-lipoxygenase (5-LOX) was examined using quantitative RT-PCR. An high-performance liquid chromatography with a UV detection method was developed to quantitatively analyze genistein-7-O-[α-rhamnopyranosyl-(1 → 6)]-β-glucopyranoside, genistein, derrisisoflavone A, lupalbigenin, and 6,8-diprenylgenistein in DS stem. The developed HPLC-UV method demonstrated high sensitivity with limits of detection and quantification ranging from 0.01 to 0.06 µg/mL and 0.03 to 0.18 µg/mL, respectively. The accuracy of the method ranged from 93.3 to 109.6%. Furthermore, the repeatability and reproducibility of the method were suitable, as indicated by the relative standard deviations of ≤ 3.02% and ≤ 6.22%, respectively. The DS extract notably inhibited NO production, exhibiting effects comparable to those of 500 µM diclofenac, and substantially suppressed the expression of iNOS, COX-2, IL-6, and 5-LOX of lipopolysaccharide (LPS)-induced genes. As to the pure isoflavone derivatives, the order of NO production inhibition was found to be genistein > lupalbigenin > derrisisoflavone A > 6,8-diprenylgenistein > genistein-7-O-[α-rhamnopyranosyl-(1 → 6)]-β-glucopyranoside. Genistein, derrisisoflavone A, and 6,8-diprenylgenistein significantly suppressed the upregulation of all LPS-induced genes. Consequently, these compounds are recommended as anti-inflammatory markers for the quantitative chemical analysis of DS.
Keywords: anti-inflammatory activity; Derris scandens; HPLC; inflammatory genes; isoflavone; Fabaceae